Chiari Malformation-I with Syringomyelia: A Non-specific Presentation and Surgical Consideration - Maharjan, Jemesh S; Shrestha, Pranaya; Chandra, Avinash; Rajbhandari, Pravesh; Acharya, Samir; Shrestha, Resha; Bhattarai, Robin; Pant, Basant (Nepal Journal of Neuroscience, 2016)
Chiari Malformation-I is a congenital disorder characterized by the anatomical defect of the base of skull with tonsillar herniation (≥5 mm) below the foramen magnum, which is detected on MRI. It has a diverse range of symptoms with non-specific presentation leading to the chances of misdiagnosis and untimely recognition of the disorder. Syringomyelia is the most common result of Chiari-I. The selection of surgical or non-surgical management depends upon the patient symptoms and the presence of absence of Syringomyelia. The objective of this case report is to give a broad perspective on Chiari Malformation-I from the symptoms and clinical findings obtained in a patient with Syringomyelia associated with Chiari Malformation-I and to discuss about the different surgical options as well as the psychological support required for the management of the condition.Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page: 105-108